School-led Initial Teacher Training: Why are schools so attracted to the idea of ‘growing their own teachers’? - Joanne Hill (Educational Futures)
School-led Initial Teacher Training (ITT) is not a new concept, the current position of schools in ITT has been developed in line with government neoliberal agendas since the 1980s. The origins of school-led ITT, however, can be traced back to the Monitorial system of the early nineteenth century where teacher helpers were drawn from more able pupils, replaced in 1846 by the Victorian Pupil-Teacher model (Dent, 1977). This paper focuses specifically on one recent school-led model, School Direct (SD), which promoted schools’ role in recruiting, training and employing teachers as a means of ‘growing their own’. The paper problematises notions of ‘growing your own’, questioning why ‘growing’ teachers has become a seemingly attractive model for schools.